Control interno administrativo y su incidencia en los ingresos propios en el departamento de recaudaciones del GAD municipal del cantón Quevedo período 2019 – 2020. - Tumbaco Rodríguez, Verónica Gabriela (2021)
The present investigation titled "The Administrative Internal Control and its incidence in the own income in the Department of collections of the Municipal GAD of the Cantón Quevedo período 2019-2020", whose objective was: To evaluate the incidence of the administrative internal control in the own income in the The department of collections of the Autonomous Decentralized Municipal Government of the Quevedo Canton, which has weaknesses in the application of the Rules that impacts on the level of collections of the Municipality, also presents difficulties in the administrative procedures that influences its own income Furthermore, there is little analysis of the efficiency and effectiveness indicators, thus generating inconsistencies in collections. The research is of a quali-quantitative nature and the methodology used allowed to address the problematic of the topic to be investigated, for it requires applying inductive, deductive, analytical, historical-logical methods, in order to evaluate and interpret the data obtained through observation, interview and relevant documentation to demonstrate the internal procedures as a collection instrument, to establish the way in which collections are carried out, compliance with regulations, administrative processes, the current procedures manual and verify the efficiency and effectiveness of those who work in the Department. As results, the shortcomings, problems and inconveniences raised within the processes and activities in the collections were evidenced, they were socialized with the pertinent authorities so that the preventive and corrective measures they deem appropriate are taken. After making the study transparent, it is intended to develop improvements that allow operating in the use and application of internal procedures. Keywords: Internal Control - Collection - Administration - Procedures - Standards